Best-case scenario robust portfolio for energy stock market. (15th December 2020) - Chen, Chen; Liu, Dinghao; Xian, Liang; Pan, Lin; Wang, Lihua; Yang, Min; Quan, Li
Abstract: Based on Markowitz mean-variance theoretical model (MV), the energy portfolio optimization problem has been extensively studied to obtain the optimal strategies of energy resource allocations and achieve the efficient usages and productions of energy. However, MV leads to the optimal energy portfolios infeasible without consideration of uncertainties. Meanwhile, dealing with the uncertain input parameters in the model, robust mean-variance model (RMV-worst) can overcome this shortcoming, but the optimal energy portfolio performances are considerably inferior. Therefore, contrary to RMV-worst, this paper analytically constructs an alternative robust portfolio model (RMV-best). Furthermore, from the energy stock market of China the data containing two motion cycles is divided into three movement statuses to verify the overall performances of the optimal energy portfolios. Finally, the comparison results add to the existing researches on energy portfolio optimization by: (i) RMV-best can validly improve the energy portfolio performances while ensuring the optimal energy portfolios feasible. (ii) The different movement statuses significantly influence on the energy portfolio performances, subsequently giving the favorable decisions of energy portfolios. (iii) The optimal energy portfolios of RMV-best are very reliable, as further indicates that RMV-best can bring about the convincing energy portfolios. Highlights: Best-case scenario robust model is built, improve energy portfolio performances. The movement statuses of stock market influence on the energy portfolio selection. The more favorable energy portfolios can be obtained for each movement status. Wide application of RMV-worst is inefficient and undesirable for energy portfolio. The optimal energy portfolios of RMV-best are reliable and profitable.